1992
DOI: 10.1002/dvg.1020130103
|View full text |Cite
|
Sign up to set email alerts
|

Developmental analysis of the cell recognition mechanism in the ciliate Euplotes raikovi

Abstract: Euplotes raikovi, like other ciliates, passes through a postconjugal immaturity, operatively identified by an apparent cell inability to form mating pairs under experimental conditions that are the same as those used for inducing mating at maturity. In cells homozygous for the gene mat-2, which controls the pheromone Er-2, Er-2 mRNA synthesis and mature Er-2 secretion were shown to start from the very beginning of the life cycle and continue throughout immaturity, although to extents estimated to be 5- to 10-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In the ciliate Euplotes raikovi, mating pheromones (euplomones) are synthesized constitutively throughout the entire clonal life cycle and in growing cells (Miceli et al, 1989;Luporini et al, 1992;Miceli et al, 1992;Vallesi et al, 1995;Luporini et al, 1995;Ortenzi et al, 2000). The gene encoding each pheromone generates at least two distinct molecules by alternative splicing, one of which is the soluble pheromone and the other a membrane-bound pheromone isoform.…”
Section: Discussionmentioning
confidence: 99%
“…In the ciliate Euplotes raikovi, mating pheromones (euplomones) are synthesized constitutively throughout the entire clonal life cycle and in growing cells (Miceli et al, 1989;Luporini et al, 1992;Miceli et al, 1992;Vallesi et al, 1995;Luporini et al, 1995;Ortenzi et al, 2000). The gene encoding each pheromone generates at least two distinct molecules by alternative splicing, one of which is the soluble pheromone and the other a membrane-bound pheromone isoform.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems reasonable to suppose that ciliates mate under similar conditions in the field as well: when and were crowding occurs, ciliates may consume the food patch quickly and then conjugate. A high density of sexually complementary conspecifics greatly increases the probability of mating, by increasing both the frequency of encounters between sexually complementary partners and the intensity of pre-conjugative interactions (Luporini et al 1992, Doerder et al 1996, Miyake 1996. Such interactions may thus be more effective in crowded patches of conspecifics.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of easily inducing conjugation by favouring pre-conjugative interactions and synchronising complementary cells (e.g. Fujishima 1988, Luporini et al 1992, Miyake 1996, Santangelo & Bruno 2001 suggested that this process could also occur frequently in nature, though both the instability of the natural environment and the basically clonal population structure of protists (Kusch & Heckmann 1996) could greatly reduce its frequency. As these studies were based on labcultured strains, they cannot provide any information about the actual incidence of conjugation in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Euplotes raikovi are unicellular ciliate organisms that synthesize and secrete constitutively their pheromones (Luporini et al 1992). Pheromones are cell typespecific and structurally homologous proteins that may act as mitogenic signals when bound to the cell from which they originate-autocrine processing-or as mating signals inducing sexual reproduction when bound to other neighboring cellsparacrine processing (Vallesi et al 1995).…”
Section: From Autocrine To Paracrine Signalingmentioning
confidence: 99%